Farmers’ Fertilizer Application Gap In Ricebased Cropping System: A Case Studyof Nepal - Baral, BR; Pande, KR; Gaihr, YK; Baral, KR; Sah, Sk; Thapa, YB (SAARC Journal of Agriculture, 2020)
Low adoption of improved agricultural practices is one of the major challenges to improve food security. A case study was carried out to assist the farmer’s fertilizer application gap in rice cultivation in Nepal. To collect data a household survey was conducted in 2017 by selecting 90 households randomly from rice growing pocket area of Banke district of Nepal. The rates of fertilizers use were assessed in relation to farm size, crop variety, irrigation etc. The applications of both organic and mineral fertilizers vary highly by farmer type. Small and medium farmers applied twice the amount of organic manure compared to large farmers. For inorganic fertilizer use, large farmers applied higher amounts of nitrogen (N) fertilizer compared to medium and small farmers. Across farmer types, a higher amount of N and P fertilizers was used for hybrid varieties than inbred varieties and in irrigated fields than in rainfed fields. The use of potassium (K) fertilizer was low and not affected by farmer type or variety. Overall, farmers used a lower amount of N and K and a higher amount of P than the recommendation. The imbalanced use of fertilizers was associated with poor access to agricultural extension services. Variations of fertilizer use among farmers and the role of extension in the adoption of improved practices are still underresearched, and hence this study exposes the need to investigate indepth knowledge, determinants of fertilizer use and role of extension education. Results from this study could be important to develop an innovative extension program using multiple channels to increase farmers’ access to and awareness regarding balanced use of fertilizers to increase soil fertility and crop productivity. SAARC J. Agri., 17(2): 267-277 (2019)